Current management options for displaced intra-articular calcaneal fractures: Non-operative, ORIF, minimally invasive reduction and fixation or primary ORIF and subtalar arthrodesis. A contemporary review. Issue 1 (March 2016) - Sharr, P.J.; Mangupli, M.M.; Winson, I.G.; Buckley, R.E.
Highlights: Contemporary review of displaced intra-articular calcaneus fracture literature. Contemporary review of management options for calcaneus fractures. Guidelines to aid decision-making for surgeons managing displaced intra-articular calcaneus fractures. Abstract: Background: Management of Displaced Intra-articular Calcaneal Fractures (DIACFs) continues to be technically demanding. The literature has not been definitive in its guidance for surgeons dealing with these injuries. Recent publications have further added to the lack of clarity. This review is intended to summarise the present state of knowledge, and provide some genuine guidance for clinicians. Objectives: To review previous research, focussing on articles published within the last fifteen years, and summarise the findings to aid surgeons in managing DIACFs with choosing best management for patients. Methods: We reviewed the best evidence and literature, focussing on articles published within the last fifteen years, and summarised findings into workable recommendations. Variables of (1) patient, (2) the associated soft tissue injury and (3) the fracture characteristics were used to aid surgeons in choosing the best of the available options for each patient that presents with a DIACF. Authors summary: Management of DIACFs can best be divided into four broad categories: (i) non-operative management, (ii) open reduction and internal fixation, (iii) minimally invasive reduction and fixation, and (iv) primary subtalar arthrodesis. The evolution of the literature would suggest orthopaedic surgeons managing calcaneus fractures should have an expert's knowledge, surgical expertise and the latest techniques to cover these four options, to tailor the treatment of DIACFs to the individual patient.